2004
DOI: 10.1386/adch.2.3.143/0
|View full text |Cite
|
Sign up to set email alerts
|

Critical absence versus critical engagement. Problematics of the crit in design learning and teaching

Abstract: This article describes a study which sets out to examine how changes in student patterns of learning, in particular the demise of the design ‘baseroom’ and the growth of online learning, might have on the crit. The study found that the crit constitutes a heightened moment of exchange between staff and students in the new landscape of learning. The crit, in this context, becomes a powerful vehicle for the induction and inculturation of students into the dominant mores and beliefs of a programme and its discipl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
30
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(30 citation statements)
references
References 2 publications
0
30
0
Order By: Relevance
“…Schrand and Eliason"s (2012) research indicates that the design critique does not always allow all types of students to participate, and students who are not confident enough to ask questions are left behind. Barrett (2000) and Percy (2004) cite frustration, alienation, and lack of student participation as outcomes of the traditional design critique. Further research yields a list of factors that may impede student learning, including the size (Blair, 2006) and dynamics of the group (Gray, 2013); language and cultural competencies (Lasserre, 2010;Wong 2011); and perceived self-efficacy (Gaffney, 2011).…”
Section: The Design Critiquementioning
confidence: 99%
“…Schrand and Eliason"s (2012) research indicates that the design critique does not always allow all types of students to participate, and students who are not confident enough to ask questions are left behind. Barrett (2000) and Percy (2004) cite frustration, alienation, and lack of student participation as outcomes of the traditional design critique. Further research yields a list of factors that may impede student learning, including the size (Blair, 2006) and dynamics of the group (Gray, 2013); language and cultural competencies (Lasserre, 2010;Wong 2011); and perceived self-efficacy (Gaffney, 2011).…”
Section: The Design Critiquementioning
confidence: 99%
“…Bourdieu (1977Bourdieu ( , 1984Bourdieu ( , 1988 argues that education involves a strong current of acculturation, where 'habitus' (as disciplinary dispositions) 'leads us to "reproduce" the social conditions of our own production' (Bourdieu 1990: 87). Many studies have pointed to the exclusionary practices and unequal relationships between students and lecturers within fine art, where the tacit acceptance of this imbalance may even be crucial to the acculturation role of the crit (Percy 2004). Those with social and cultural capital are accepted as promising future members of the community, while those who are not, become alienated from the discourse and performance of the assessment practices.…”
Section: Assumptions and Approaches To Judgementmentioning
confidence: 99%
“…However, some argue that a more positive view of 'cultural capital' may create possibilities for power differentials within communities to be recognised and reversed (Horton 2007). With revision, it is argued that the crit in particular can become an event that explicitly and consciously provides students with epistemological access (Percy 2004), and may promote political and social values amongst students (McCoy 1993).…”
Section: Assumptions and Approaches To Judgementmentioning
confidence: 99%
“…Tacit practice has been identified as an important element of assessment practice (Sambell and McDowell 1998). In a study of studio-based dialogic feedback (otherwise known as the Crit), Percy (2004) identified that art and design lecturers use very imprecise language and that they often resort to gestural language when discussing students' artwork. The lecturers in Percy's study wrestle with the challenge of trying to 'name what they know' (Polanyi 1998).…”
Section: Literature Overviewmentioning
confidence: 99%